If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8p-3=3p-3
We move all terms to the left:
8p-3-(3p-3)=0
We get rid of parentheses
8p-3p+3-3=0
We add all the numbers together, and all the variables
5p=0
p=0/5
p=0
| -52=4q | | 0=-15x^2+110x+500 | | (x+10)=(9x+30) | | 20w=480 | | 2m=-7.3 | | 21r=609 | | (12m-7)=(8m+5) | | 23j=-736 | | a/411/12=1/2-a/6 | | (a)/(4)(11)/(12)=(1)/(2)-(a)/(6) | | 66=3t | | 11x-29=8x+1 | | .83(x+10)=20 | | 12+7x-23+3x=3+3x-5 | | 3x+22=33 | | 17x+10x-4x=-8-47 | | 3x^2-9=48 | | -y=69 | | -3(7-11c)=-18 | | 4x-100=1.12(x+47) | | 30+4x=2x | | 9.67=x^2-5x | | -35=5j | | 2(-3+3x)=34(2x+1) | | 5(1+6x)=-175 | | X2-0.6=1.7x | | .7+x=-1.34 | | 2(3x+15)=180 | | 9.67=x(x-5) | | -2(n+3)+4=8 | | 7/20x=90 | | 3=r/7 |